2020
DOI: 10.2337/dc19-2424
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antihyperglycemic Medications in U.S. Adults: An Analysis of the National Health and Nutrition Examination Survey

Abstract: To examine trends in the use of diabetes medications and 2) to determine whether physicians individualize diabetes treatment as recommended by the American Diabetes Association (ADA). RESEARCH DESIGN AND METHODSWe conducted a retrospective, cross-sectional analysis of 2003-2016 National Health and Nutrition Examination Survey (NHANES) data. We included people ‡18 years who had ever been told they had diabetes, had an HbA 1c >6.4%, or had a fasting plasma glucose >125 mg/dL. Pregnant women and patients aged <20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 35 publications
(20 reference statements)
2
41
3
1
Order By: Relevance
“…The socioeconomic index ranged between 13.98 and 90.45,15 and occupation was categorized into upper (socioeconomic index ≥50), lower (socioeconomic index <50, including retirees16 and students), and unemployment. Health insurance was categorized into private health insurance (including any private health insurance, Medi-Gap, or single-service plan), public health insurance only (including Medicare, Medicaid, State Children’s Healthcare Plan, military healthcare, Indian Health Service, State Sponsored Health Plan, or other government programme), and no health insurance 17. An overall SES variable was created using latent class analysis based on family income level, occupation, education level, and health insurance (each factor had three levels) 7.…”
Section: Methodsmentioning
confidence: 99%
“…The socioeconomic index ranged between 13.98 and 90.45,15 and occupation was categorized into upper (socioeconomic index ≥50), lower (socioeconomic index <50, including retirees16 and students), and unemployment. Health insurance was categorized into private health insurance (including any private health insurance, Medi-Gap, or single-service plan), public health insurance only (including Medicare, Medicaid, State Children’s Healthcare Plan, military healthcare, Indian Health Service, State Sponsored Health Plan, or other government programme), and no health insurance 17. An overall SES variable was created using latent class analysis based on family income level, occupation, education level, and health insurance (each factor had three levels) 7.…”
Section: Methodsmentioning
confidence: 99%
“…Among the many oral hypoglycaemic agents that are available for treatment of type 2 diabetes, metformin is considered as a first‐line drug for pharmacotherapy 1–3 . According to US and European guidelines, sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors are considered second‐line drugs after metformin for patients with type 2 diabetes and atherosclerotic cardiovascular disease (ASCVD) or chronic kidney disease 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite ADA treatment guidelines, 3 the use of DPP‐4is (12.5% in a large US cohort from 2016 to 2018) 7 with no demonstrated CVD benefit continues to be higher than SGLT‐2is and GLP‐1RAs (9.0% and 7.9%, respectively), 7 agents with well‐documented CV benefits. Another study showed that drug choice in US patients with T2D did not vary by presence of CVD 8 . More closely aligning US prescribing practices with current treatment guidelines may lead to efficient utilization of healthcare resources.…”
Section: Introductionmentioning
confidence: 99%